MEDICAL AND DENTAL PROBLEMS AMONG TRANSGENDERS – AN UNTOUCHED TOPIC: A REVIEW - RAFIQUL ISLAM; MOHAMMAD KHURSHEED ALAM; MOHD FADHLI KHAMIS (International Journal of Pharma and Bio Sciences, 2015)
The aim of the study was to review the transgender in relation medical and dental difficulties. The electronic data base was searched, followed the combination of key word. Discrimination in patient care for transgender has been well-documented in many assessment literatures, although there is little in the literatures about healthcare providers’ attitudes and behavior toward transgender people. The Medical problems among transgender were investigated minute; there was no such dental investigation for the transgender community. As separate gender there may be a proper guidelines and investigation for their medical and dental treatment.